(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Sunflower (Helianthus annuus) is one of the strongest allelopathic crops through incorporation of its residue in soil to control weed. An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh, during the period from June to December 2017 to evaluate the effect of sunflower crop residues on weed management and performance of transplanted aman rice. The experiment consisted of four sunflower residues such as 0, 0.5, 1.0, 2.0 t ha-1 and four rice varieties i.e; BRRI dhan57, Binadhan-7, Binadhan-15 and Binadhan-16. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Five weed species belonging to four families infested the experimental plots. Weed population and weed dry weight were significantly affected by cultivar and crop residues treatment. The highest percent weed inhibition was found in sunflower crop residues at 2 t ha-1 treatment which was 47.29, 52.03, 51.28, 71.41 and 70.44 percent for Shama (Echinochloa crusgalli), Amrul (Oxalis corniculata L.), Panikachu (Monochoria vaginalis, Sabujnakful (Cyperus difformis) and Chesra (Scirpus juncoides), respectively. The maximum weed growth was noticed with the cultivar BRRI dhan57 variety and the minimum was found in the cultivar Binadhan-16. The grain yield as well as the yield contributing characters produced by Binadhan-16 was the highest among the studied varieties. The highest reduction of grain yield was obtained in no crop residue treatment. The highest number of effective tillers hill-1, number of grains panicle-1, 1000-grain weight, grain and straw yields were observed in sunflower residues at 2.0 t ha-1 treatment. Binadhan-16 produced the highest grain and straw yields with sunflower residues 2.0 t ha-1 treatment. Results of this study indicate that sunflower residues showed potentiality to inhibit weed growth and it has a significant effect on the yield of transplanted aman rice. Therefore, sunflower residues might be used as an alternative way for weed management effective as well as obtaining higher yield of T. aman rice. J Bangladesh Agril Univ 18(3): 557–564, 2020 https://doi.org/10.5455/JBAU.18316